TRASH TALKING DALAM KOMUNIKASI VIRTUAL - Rosniar, Rosniar; Syam, Syahrianti; Wardana, Dimas Alfareza (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
This research discusses trash talking communication behavior that occurs in the online game PUBG Mobile through virtual communication features, namely chat and voice chat, which allow users to interact with other players. This research aims to analyze the trash talking behavior of Nonstra Bone teenagers in playing the online game PUBG mobile. The type of research used is descriptive qualitative. Primary data was obtained based on the results of observations and interviews with the Nostra Bone youth group, a PUBG Mobile online game community in Bone Regency, South Sulawesi Province. Research shows that the trash talking behavior carried out by Nostra Bone teenagers when playing the online game PUBG Mobile is that the motivation and duration of playing PUBG Mobile varies depending on the preferences of each player, the use of chat and voice chat features which are used to communicate virtually between players, and trash. Talking when playing PUBG mobile is a form of aggressive communication carried out by players, including flaming, namely sending offensive chats and voice chats in the form of using harsh words, insulting or demeaning other players. Abstrak Penelitian ini membahas tentang perilaku komunikasi trash talking yang terjadi dalam game online PUBG Mobile melalui fitur komunikasi virtual yaitu chat dan voice chat yang memungkinkan pengguna untuk berinteraksi dengan pemain lain. Penelitian ini bertujuan untuk menganalisis perilaku trash talking remaja Nonstra Bone dalam bermain game online PUBG mobile. Jenis penelitian yang digunakan yaitu deskriptif kualitatif. Data primer didapatkan berdasarkan hasil observasi dan wawancara pada kelompok remaja Nostra Bone, sebuah komunitas game online PUBG Mobile di Kabupaten Bone, Provinsi Sulawesi Selatan. Penelitian menunjukkan bahwa perilaku trash talking yang dilakukan remaja Nostra Bone dalam bermain game online PUBG Mobile yaitu motivasi dan durasi bermain PUBG Mobile yang bervariasi tergantung pada preferensi masing-masing pemain, penggunaan fitur chat dan voice chat yang digunakan untuk berkomunikasi secara virtual antarpemain, dan trash talking dalam bermain PUBG mobile berupa bentuk komunikasi agresif yang dilakukan oleh pemain di antaranya flaming, yaitu mengirim chat dan voice chat yang bersifat ofensif berupa penggunaan kata-kata kasar, menghina, atau merendahkan pemain lain.